Characterization of cachexia in the human fibrosarcoma HT‐1080 mouse tumour model. Issue 6 (13th September 2020) - Bernardo, Barbara; Joaquim, Stephanie; Garren, Jeonifer; Boucher, Magalie; Houle, Christopher; LaCarubba, Brianna; Qiao, Shuxi; Wu, Zhidan; Esquejo, Ryan M.; Peloquin, Matthew; Kim, Hanna; Breen, Danna M.
Abstract: Background: Cancer cachexia is a complex metabolic disease with unmet medical need. Although many rodent models are available, none are identical to the human disease. Therefore, the development of new preclinical models that simulate some of the physiological, biochemical, and clinical characteristics of the human disease is valuable. The HT‐1080 human fibrosarcoma tumour cell line was reported to induce cachexia in mice. Therefore, the purpose of this work was to determine how well the HT‐1080 tumour model could recapitulate human cachexia and to examine its technical performance. Furthermore, the efficacy of ghrelin receptor activation via anamorelin treatment was evaluated, because it is one of few clinically validated mechanisms. Methods: Female severe combined immunodeficient mice were implanted subcutaneously or heterotopically (renal capsule) with HT‐1080 tumour cells. The cachectic phenotype was evaluated during tumour development, including body weight, body composition, food intake, muscle function (force and fatigue), grip strength, and physical activity measurements. Heterotopic and subcutaneous tumour histology was also compared. Energy balance was evaluated at standard and thermoneutral housing temperatures in the subcutaneous model. The effect of anamorelin (ghrelin analogue) treatment was also examined. Results: The HT‐1080 tumour model had excellent technical performance and was reproducible across multiple experimental conditions. Heterotopic and subcutaneous tumour cell implantation resulted in similar cachexia phenotypes independent of housing temperature. Tumour weight and histology was comparable between both routes of administration with minimal inflammation. Subcutaneous HT‐1080 tumour‐bearing mice presented with weight loss (decreased fat mass and skeletal muscle mass/fibre cross‐sectional area), reduced food intake, impaired muscle function (reduced force and grip strength), and decreased spontaneous activity and voluntary wheel running. Key circulating inflammatory biomarkers were produced by the tumour, including growth differentiation factor 15, Activin A, interleukin 6, and TNF alpha. Anamorelin prevented but did not reverse anorexia and weight loss in the subcutaneous model. Conclusions: The subcutaneous HT‐1080 tumour model displays many of the perturbations of energy balance and physical performance described in human cachexia, consistent with the production of key inflammatory factors. Anamorelin was most effective when administered early in disease progression. The HT‐1080 tumour model is valuable for studying potential therapeutic targets for the treatment of cachexia.